Visualizing traumatic stress-induced structural plasticity in a medial amygdala pathway using mGRASP - Bartsch, Caitlyn J.; Jacobs, Jessica T.; Mojahed, Nooshin; Qasem, Elana; Smith, Molly; Caldwell, Oliver; Aaflaq, Sophia; Nordman, Jacob C. (Frontiers in Molecular Neuroscience, 2023)
Traumatic stress has been shown to contribute to persistent behavioral changes, yet the underlying neural pathways are not fully explored. Structural plasticity, a form of long-lasting neural adaptability, offers a plausible mechanism. To scrutinize this, we used the mGRASP imaging technique to visualize synaptic modifications in a pathway formed between neurons of the posterior ventral segment of the medial amygdala and ventrolateral segment of the ventromedial hypothalamus (MeApv-VmHvl), areas we previously showed to be involved in stress-induced excessive aggression. We subjected mice (7–8 weeks of age) to acute stress through foot shocks, a reliable and reproducible form of traumatic stress, and compared synaptic changes to control animals. Our data revealed an increase in synapse formation within the MeApv-VmHvl pathway post-stress as evidenced by an increase in mGRASP puncta and area. Chemogenetic inhibition of CaMKIIα-expressing neurons in the MeApv during the stressor led to reduced synapse formation, suggesting that the structural changes were driven by excitatory activity. To elucidate the molecular mechanisms, we administered the NMDAR antagonist MK-801, which effectively blocked the stress-induced synaptic changes. These findings suggest a strong link between traumatic stress and enduring structural changes in an MeApv-VmHvl neural pathway. Furthermore, our data point to NMDAR-dependent mechanisms as key contributors to these synaptic changes. This structural plasticity could offer insights into persistent behavioral consequences of traumatic stress, such as symptoms of PTSD and social deficits.